Effects of a Digital Self-care Intervention in Adults with COPD: A Pilot Study. (September 2020) - Bugajski, Andrew; Frazier, Susan K.; Cousin, Lakeshia; Rechenberg, Kaitlyn; Brown, Jaelyn; Lengerich, Alexander J.; Moser, Debra K.; Lennie, Terry A.
Self-care improves quality of life, and reduces exacerbations and mortality risk in people with chronic obstructive pulmonary disease (COPD). The purpose of this report is to describe the development and testing of the feasibility and acceptability of a digital, educational self-care intervention designed to improve self-care ability, adherence, knowledge, somatic symptoms, anxiety, and depressive symptoms. This pilot study was a quasi-experimental, repeated measures design. Self-care behaviors were identified, and educational modules were developed and built into a web-based platform. Twenty participants were enrolled to determine feasibility, acceptability, and preliminary efficacy. The intervention was deemed acceptable and feasible as evidenced by > 95% completion rates and high degree of participation. Overall, the intervention was well received and is feasible for future home-based interventions in those with COPD. Results included significant improvements in adherence and knowledge, and significant associations between self-care ability, adherence, and depressive symptoms.